Organisation and delivery of supportive services for patients with prostate cancer in the National Health Service in England and Wales: a national cross-sectional hospital survey and latent class analysis - Melanie Morris; Ajay Aggarwal; Jan van der Meulen; Noel Clarke; Adrian Cook; Heather Ann Payne; Joanna Dodkins; Julie Nossiter; Steve Prust; Steve Waller (BMJ Open, 2023)
Objectives We assessed how often National Health Service (NHS) hospitals reported that they had specific supportive services for patients with prostate cancer available onsite, including nursing support, sexual function and urinary continence services, psychological and genetic counselling, and oncogeriatric services. We identified groups of hospitals with similar patterns of supportive services.Design/setting We conducted an organisational survey in 2021 of all NHS hospitals providing prostate cancer services in England and Wales. Latent class analysis grouped hospitals with similar patterns of supportive services.Results In 138 hospitals, an advanced prostate cancer nurse was available in 125 hospitals (90.6%), 107 (77.5%) had a clinical nurse specialist (CNS) attending all clinics, 103 (75.7%) had sexual function services, 111 (81.6%) had continence services and 93 (69.4%) psychological counselling. The availability of genetic counselling (41 hospitals, 30.6%) and oncogeriatric services (15 hospitals, 11.0%) was lower. The hospitals could be divided into three groups. The first and largest group of 85 hospitals provided the most comprehensive supportive services onsite: all hospitals had a CNS attending all clinics, 84 (98.8%) sexual function services and 73 (85.9%) continence services. A key characteristic of the second group of 31 hospitals was that none had a CNS attending all clinics. A key characteristic of the third group of 22 hospitals was that none had sexual function services available. The hospitals in the largest group were more likely to run joint clinics (p<0.001) and host the regional specialist multidisciplinary team (p=0.002).Conclusions There is considerable variation in supportive services for prostate cancer available onsite in NHS hospitals in England and Wales. Availability of genetic counselling and oncogeriatric services is low. The different patterns of supportive services among hospitals demonstrate that initiatives to improve the availability of the entire range of supportive services to all patients should be carefully targeted.